Implementing the Circular Economy in SMEs: A Modeling Review from the Behavioral Aspect - Nasoha, Mohamad; Ngarbingan, Hubertina Karolina; Ginting, Ginta (Journal of International Conference Proceedings, 2023)
Circular Economy (CE) is an alternative concept to switch from a linear economy (take-make-dispose) to make-use-recycle. The CE concept is elaborated as a future policy in Indonesia's Vision 2045 to immediately carry out economic transformation. Practically, there are big challenges and focus on the current actual conditions. So far, the CE practice approach has been more directed at technology and manufacturing changes. Therefore, seeing the role of industry players is important to accelerate CE practices. In terms of the possibility of their resources, large business doers can accommodate the use of ES methods. However, SME players believe that CE implementation practices are still not optimal. For SME players, implementing the CE business model will have a faster impact compared to large businesses because of two things: closer to the end customer and a decentralized production system. Thus, investigations into CE practices in SMEs are important to provide an understanding of the extent to which SMEs can implement practices within a practical and efficient scope. This paper describes the findings in the field from 75 respondents (SMEs) in Malang (East Java) regarding CE practices from a behavioral aspect. The result of this study is expected to be preliminary research in the development of the behavior model of CE practices in SMEs.